1997
DOI: 10.1902/jop.1997.68.5.467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Mechanical and Antimicrobial Periodontal Therapy

Abstract: The aim of this investigation was to evaluate the effect of smoking on the outcome of periodontal therapy. The study consisted of 54 patients who participated in a 4-group parallel-arm clinical trial on the efficacy of three locally delivered antimicrobial systems as adjuncts to scaling and root planing in the treatment of sites with persistent pocketing after a course of scaling and root planing. These groups included scaling and root planing either alone (S) (n = 3), or in conjunction with the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
91
2
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 23 publications
15
91
2
7
Order By: Relevance
“…Kinane and Radvar (1997) found that the response to non-surgical mechanical therapy is particularly poor in deep pockets in smokers. Although the attachment gain was also greater among the non-smokers than the smokers, this was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Kinane and Radvar (1997) found that the response to non-surgical mechanical therapy is particularly poor in deep pockets in smokers. Although the attachment gain was also greater among the non-smokers than the smokers, this was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Studies during later years have confirmed these observations and contributed additional evidence that the gingival inflammatory response is altered by smoking. [5][6][7][8][9][10][11][12][13][14][15] The anti-hemorrhagic and anti-inflammatory effects imply that typical symptoms of inflammation, such as redness, bleeding, and edema appear comparably late in the disease process, if at all, in the average smoker patient. Interestingly, in smokers undergoing smoking cessation programs, gingival bleeding and gingival blood flow, as well as gingival crevicular fluid flow, increase and normalize toward non-smoker levels after quitting.…”
Section: Smoking and Periodontal Inflammationmentioning
confidence: 99%
“…This mechanism is possibly caused by chemical substances in cigarettes that can provide nutrition for candida, local changes in epithelium that which leads to candida colonization [12,14,16], decreased antibodies in saliva and hyposalivation [8,24,32,33]. Duration and amount of smoking would have a different impact on number of the candida colonies [12].…”
Section: Resultsmentioning
confidence: 99%